Deep learning based early Glaucoma detection - Islam, Aabrar; Haque, Ayen Aziza; Tasnim, Najifa; Waliza, Simin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.